Effects of zinc supplementation on sexual behavior of male rats - DMAB Dissanayake; P S Wijesinghe; W D Ratnasooriya; S Wimalasena (Wolters Kluwer Medknow Publications, 2009)
Context: Effects of zinc on male sexual competence are poorly understood. Aim: To study the effects of different doses of zinc on the sexual competence of males using a rat model. Materials and Methods: Three subsets (eight in each subset) of sexually experienced adult male rats were supplemented with three different oral doses of zinc sulphate (a daily dose of 1 mg, 5 mg and 10 mg respectively) for two weeks. A subset of eight animals without zinc supplementation was used as the control group Sexual behavior was observed by placing them individually in cages with receptive females. Statistical Analysis : Data analysis was done using SPSS v10 for windows computer software. Results: Supplementation of 5 mg of zinc/day for two weeks led to a prolongation of ejaculatory latency; 711.6 sec. (SEM 85.47) vs. 489.50 sec. (SEM 67.66), P < 0.05 and an increase in number of penile thrusting; 52.80 (SEM 11.28) vs. 26.50 (SEM 6.17), P < 0.05, compared to controls. The same group had elevated prolactin (PRL) and testosterone (T) levels compared to controls at the end of treatment period; PRL- 7.22 ng/dl (SEM 3.68) vs. 2.90 ng/dl (SEM 0.34) and T- 8.21 ng/ml (SEM 6.09) vs. 2.39 ng/ml (SEM 1.79), P < 0.05. In contrast, reduction of libido was evident in the same group, but this effect was not statistically significant ( P > 0.05). However, partner preference index was positive and 5 mg zinc supplementation did not exert a significant adverse effect on the muscle strength and co-ordination. The subset of rats supplemented with 1 mg/day did not show a difference from the control group while supplementation with 10 mg/day led to a reduction of the libido index, number of mounts and intromissions. Conclusions : Zinc therapy improves sexual competence of male rats; the effect is dose dependent. Increase in the T levels is beneficial in this regard. However, increase in PRL is responsible for the reduced libido index. Further studies on pigs and monkeys are needed to evaluate the therapeutic use of zinc in sexual dysfunction.